2013
DOI: 10.11609/jott.o3595.4953-61
|View full text |Cite
|
Sign up to set email alerts
|

Status of reptiles in Meghamalai and its environs, Western Ghats, Tamil Nadu, India

Abstract: Reptiles of MeghamalaiBhupathy & Sathishkumar 4954been made to study the reptiles of this area (Bhupathy et al. 2009;Chandramouli & Ganesh 2010). In the present paper, we update the reptile fauna of Meghamalai area and provide data on species richness, composition, distribution with respect to Indian biogeographic zones and their threat status. MethodsMeghamalai (9 0 30'-10 0 30'N & 77 0 -78 0 30'E) is located in Theni Forest Division (Theni District) of Tamil Nadu state (Fig. 1). Herpetofauna of the area was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…A study conducted by Nitin [8] concluded the new locality of C. h. monticollaris in Vansda National Park, Navsari, Gujarat, India. Subsequently, Bhupathy and Sathishkumar [9] reported C. h. (Table 1) and few belongs to rare category that is globally threatened. Hence, there is an urgent need for strategies to conserve these rare and threatened snakes in STR and PBR.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Nitin [8] concluded the new locality of C. h. monticollaris in Vansda National Park, Navsari, Gujarat, India. Subsequently, Bhupathy and Sathishkumar [9] reported C. h. (Table 1) and few belongs to rare category that is globally threatened. Hence, there is an urgent need for strategies to conserve these rare and threatened snakes in STR and PBR.…”
Section: Resultsmentioning
confidence: 99%
“…Time-constrained visual encounter surveys (TCVES) and quadrat search (size: 10x10 m) as described in Heyer et al (1994) were used for data collection in three belt transects for a period of two years between December 2006 and November 2008 on a seasonal basis; dry (December-May) and wet (June-November) seasons (also see Bhupathy et al 2009;Bhupathy & Sathishkumar 2013). These transects (fixed width of 1000m) were located in Mavadi, Suruli and Vellimalai areas of Meghamalai (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Very few recent workers have reported the species from India. Malhotra & Davis (1991) report sighting of three specimens in rock piles situated within the montane grasslands atop the Srivilliputhur Hills, at 1290-1690 m. Recent reports originated from Nallamalai Hills in Andhra Pradesh (Rao et al 2005), Kambakkam Hills in Andhra Pradesh (Ganesh & Asokan 2010), Kaas plateau in Maharashtra (Chikane & Bhosale 2012), Meghamalai Hills in Tamil Nadu (Bhupathy & Sathishkumar 2013), Kalakadu Mundanthurai Tiger Reserve in Tamil Nadu (Narayanan 2016), and Vellore as well as the Gingee Hills of the Eastern Ghats in Tamil Nadu (Ganesh et al 2018). Bhattarai et al (2018) also reported the species from Nepal (Chitwan, Makwanpur).…”
Section: Redescription Of Liopeltis Calamaria Indicamentioning
confidence: 99%